IDENTIFIKASI KANDUNGAN TIMBAL (Pb) PADA IKAN YANG DIJUAL OLEH PENGEPUL IKAN SUNGAI DONAN CILACAP - Annisya Rahmadina Jannati; Wiwik Wijaningsih; Yuwono Setiadi (JURNAL RISET GIZI, 2014)
Background : According to the research results of Hernayanti (2006) the content of Cd heavy metals in waters and sendiments ranged between 0.14-1.03 ppm and 0.85-2.75 ppm, while the heavy metal content of Pb in water and successive metals ranging between 0.085-1.1 ppm and 11.3-18.5 ppm. Fish are creatures that are sensitive to pollution of heavy metals so they can be used as indicators of water pollution.Objective : The purpose of this study was to determine the lead content in layur fish, three waja fish, anchovy, mullet, and keeper fish which are sold in the Donan River Pengepul Cilacap. The method used in this study is descriptive analysis that is to determine the description of lead levels in these fish. Lead levels were tested using the SSA method (Atomic Absorption Spectrophotometry).Result : The test results of lead levels using the SSA (Atomic Absorption Spectrophotometer) method showed that of 5 fish samples sold by 5 collectors in the Donan River Cilacap, lead was detected with layur content 0.143 mg / kg, mullet fish 0.271 mg / kg, anchovy 0.309 mg / kg, three waja fish 0.412 mg / kg, and goalkeeper 0.640 mg / kg.Conclution : The conclusion of this study was detected the content of timbale in layur fish, three waja fish, anchovy, mullet, and keeper fish. The highest lead content exceeds the threshold that has been determined by SNI, namely in three waja fish and keeper fish.